2019
DOI: 10.1021/acs.langmuir.9b00911
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Force and Torque Balance for Colloid Transport: Predicting Attachment and Mobilization under Favorable and Unfavorable Conditions

Abstract: Colloid attachment and detachment behaviors concern a wide range of environmental contexts but have typically been mechanistically predicted exclusive of one another despite their obvious coupling. Furthermore, previous mechanistic prediction often addressed packed column contexts, wherein specific forces and torques on the colloid could not be well-constrained, preventing robust predictions. These weaknesses were addressed through direct observation experiments under conditions where perfect sink assumptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 51 publications
4
32
0
Order By: Relevance
“…3A. As particle injection continues, these deposits continue to grow, as shown in movie S2, suggesting that the hydrodynamic stresses due to fluid flow are sufficient to overcome any possible electrostatic repulsion between like-charged particles, detailed further in the Supplementary Materials, although nanoscale heterogeneity in the colloidal interactions may also play a role (49). This observation is consistent with previous findings in 2D media (24)(25)(26)(27)(28)32).…”
Section: Dynamics Of Positively Charged Colloidal Particlessupporting
confidence: 89%
See 3 more Smart Citations
“…3A. As particle injection continues, these deposits continue to grow, as shown in movie S2, suggesting that the hydrodynamic stresses due to fluid flow are sufficient to overcome any possible electrostatic repulsion between like-charged particles, detailed further in the Supplementary Materials, although nanoscale heterogeneity in the colloidal interactions may also play a role (49). This observation is consistent with previous findings in 2D media (24)(25)(26)(27)(28)32).…”
Section: Dynamics Of Positively Charged Colloidal Particlessupporting
confidence: 89%
“…We use the Parti-Suite framework (59) to examine the interactions between single particles or clusters of particles and the glass beads making up the solid matrix. In this framework, Lagrangian trajectories that explicitly incorporate the forces and torques on particles (49) are simulated in a Happel sphere-in-cell model of the pore space surrounding an individual bead (37). Previous work has established the ability of this framework to quantitatively model particle deposition and erosion from surfaces under the influence of imposed flow (49).…”
Section: List Of Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that colloid transport and retention in porous media are generally governed by advection, dispersion, and inactivation, as well as by colloid interactions with various interfaces (Keswick & Gerba, 1980; Schijven & Hassanizadeh, 2000). Based on years of research, it is widely accepted that due to their small size, colloidal suspensions moving through porous media are excluded from pores through which they physically cannot fit (i.e., straining; Bradford & Bettahar, 2005), they have limited diffusivity (James, Wang, & Chrysikopoulos, 2018; Soto‐Gómez, Perez‐Rodriguez, Vazquez Juiz, Lopez‐Periago, & Paradelo Perez, 2019; Yu et al, 2019), and are generally electrostatically repelled from like‐charged porous media surfaces (Johnson, Rasmuson, Pazmino, & Hilpert, 2018; Rasmuson, VanNess, Ron, & Johnson, 2019; VanNess, Rasmuson, Ron, & Johnson, 2019). Because of these features, their transport is both enhanced and impeded in the subsurface, compared to non‐sorbing solutes (Bradford, Šimůnek, Bettahar, van Genuchten, & Yates, 2003; McCarthy & Zachara, 1989; McDowell‐Boyer, Hunt, & Sitar, 1986).…”
Section: Introductionmentioning
confidence: 99%